Cardiopulmonary and Muscular Interactions: Potential Implications for Exercise (In)tolerance in Symptomatic Smokers Without Chronic Obstructive Pulmonary Disease - Muller, Paulo de Tarso; Barbosa, Gisele Walter; O’Donnell, Denis E.; Neder, J Alberto (Frontiers in Physiology, 2019)
Smoking and physical inactivity are important preventable causes of disability and early death worldwide. Reduced exercise tolerance has been described in smokers, even in those who do not fulfill the extant physiological criteria for chronic obstructive pulmonary disease (COPD) and are not particularly sedentary. In this context, it is widely accepted that exercise capacity depends on complex cardio-pulmonary interactions which support oxygen (O2) delivery to muscle mitochondria. Although peripheral muscular factors, O2 transport disturbances (including the effects of increased carboxyhemoglobin) and autonomic nervous system unbalance have been emphasized, other derangements have been more recently described, including early microscopic emphysema, pulmonary microvascular disease, ventilatory and gas exchange inefficiency, and left ventricular diastolic dysfunction. Using an integrative physiological approach, the present review summarizes the recent advances in knowledge on the effects of smoking on the lung-heart-muscle axis under the stress of exercise. Special attention is given to the mechanisms connecting physiological abnormalities such as early cardio-pulmonary derangements, inadequate oxygen delivery and utilization, and generalized bioenergetic disturbances at the muscular level with the negative sensations (sense of heightened muscle effort and breathlessness) that may decrease the tolerance of smokers to physical exercise. A deeper understanding of the systemic effects of smoking in subjects who did not (yet) show evidences of COPD and ischemic heart disease – two devastating smoking related diseases – might prove instrumental to fight their ever-growing burden.